The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/er.4725
|View full text |Cite
|
Sign up to set email alerts
|

Design of diatomite-based hydrated salt composites with low supercooling degree and enhanced heat transfer for thermal energy storage

Abstract: Summary In this work, diatomite (DM) was calcined at 400°C to obtain the pure surface and pores (DM‐1); then, the three kinds of shape‐stable composite phase change materials (ss‐CPCMs) of CaCl2·6H2O (CCH)/DM‐1, CH3COONa·3H2O (SAT)/DM‐1, and Na2SO4·10H2O (SSD)/DM‐1 were prepared by impregnation method. The hydrated salts were uniformly adsorbed on the surfaces and into the pores of DM‐1 by capillary action and surface tension. The addition of nucleating agent effectively reduced the supercooling degrees of hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The sample with the 70% loading demonstrated stable phase transition temperature after 1000 thermal cycles, yet the LHS capacity reduced to 163.1 J/g due to the mass loss of about 2.2 wt%. Yang et al reported on the preparation of hydrated salt/diatomite composites with reduced supercooling and enhanced thermal conductivity [104]. The three types of composites were prepared by mechanical impregnation of CaCl 2 •6H 2 O, CH 3 COONa•3H 2 O, and Na 2 SO 4 •10H 2 O into diatomite particles.…”
Section: Diatomite-based Pcm Compositesmentioning
confidence: 99%
“…The sample with the 70% loading demonstrated stable phase transition temperature after 1000 thermal cycles, yet the LHS capacity reduced to 163.1 J/g due to the mass loss of about 2.2 wt%. Yang et al reported on the preparation of hydrated salt/diatomite composites with reduced supercooling and enhanced thermal conductivity [104]. The three types of composites were prepared by mechanical impregnation of CaCl 2 •6H 2 O, CH 3 COONa•3H 2 O, and Na 2 SO 4 •10H 2 O into diatomite particles.…”
Section: Diatomite-based Pcm Compositesmentioning
confidence: 99%
“…At present, many researchers pay more attention to the improvement of thermal conductivity and supercooling suppression. However, while solving the above problems (add additives), the corresponding heat storage capacity will decrease. How to further improve the packaging performance is of great significance to the energy storage application of composite PCMs. In recent years, pore minerals have been studied extensively, and expanded vermiculite (EVM) has become a typical representative material with its unique layered pore structure, high porosity, and large pore volume.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sugar alcohols exhibit ultra-high and unstable supercooling and low thermal conductivity, which are seriously adverse to their application. [4][5][6] Form-stable PCMs, in which traditional solid-liquid PCMs are confined in the inner spaces of supporting materials, can solve the problem of possible leakage of liquid PCMs. 7 The thermal energy is stored by the solidliquid PCMs, while the supporting materials maintain the solid shape of the form-stable PCMs.…”
Section: Introductionmentioning
confidence: 99%
“…7 The thermal energy is stored by the solidliquid PCMs, while the supporting materials maintain the solid shape of the form-stable PCMs. The supporting materials for form-stable PCMs can be ether inorganics such as diatomite, 6 SiO 2,8 TiO 2 9 and fly ash, 10 etc., or polymers such as polymethyl methacrylate, 11 polyurethane, 12 resin, 13 and polyaniline (PANI), 14,15 etc. Graphite-based materials are another kind of important supporting materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation